Phage biocontrol of enteropathogenic and Shiga toxin-producing Escherichia coli during milk fermentation - Tomat, David Damian (2013)
Two bacteriophages, isolated from faeces, were assayed as biocontrol agents of pathogenic Escherichia coli during milk fermentation. Phage DT1 was tested on the strain E. coli DH5a, one enteropathogenic E. coli (EPEC) strain and one Shiga toxigenic E. coli O157:H7 (STEC) strain. Phage DT6 was tested on two STEC strains (O157:H7 and non-O157). One additional assay was performed by using a cocktail of both phages against the O157:H7 STEC strain. Streptococcus thermophilus 10-C, the strain used as lactic starter, reached 109 CFU ml 1 after 4 h, while pH values fell to 45 after 8 h, regardless of the presence of E. coli strains and/or phages. In absence of phages, E. coli strains reached 4–6 log CFU ml 1 at 5–6 h. Escherichia coli DH5a and O157:H7 STEC strains were rapidly and completely inactivated by phage DT1 and phage cocktail, respectively, while O157:H7 STEC was completely inactivated either by DT1 or by DT6, after 8 h. The EPEC strain was not detected at 1 h (<10 CFU ml 1 ) but grew afterwards, though at lower rates than without phage. For non-O157:H7 STEC, reductions lower than 1 log CFU ml 1 were observed for all sampling times. Phages DT1 and DT6, either individually or as a cocktail, effectively reduce O157:H7 STEC counts during milk fermentation, without compromising the starter culture performance.